Analisis Dampak Ekonomi dan Sosial Usaha Kuliner UMKM terhadap Masyarakat Lokal: Studi Kelayakan Bisnis Abdar Dimsum - Asmita, Andhini; Paluvi, Retno; Rezeki, Tri Putri; Vientiany, Dini (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the economic and social impacts of the Abdar Dimsum MSME culinary business on the local community in the Mabar Hilir area, Medan City, based on a business feasibility study. The research method used is a qualitative method with a literature study approach, analysis of business feasibility study reports, and consumer survey data. The results show that Abdar Dimsum provides a positive economic impact through increased business owner income, daily turnover stability, and involvement in the local supply chain that creates an economic multiplier effect. From a social perspective, this business serves as an inclusive social interaction space by providing affordable food products for various levels of society, thereby supporting social inclusion and strengthening the relationship between business owners and consumers. Thus, the Abdar Dimsum MSME culinary business is not only business-friendly but also contributes sustainably to strengthening the economy and social cohesion of the local community.